THE EFFECT OF PRODUCT QUALITY, PRICE, AND SALES PROMOTION ON THE PURCHASE OF HONDA MOTORCYCLES ON CV. TOLITOLI ANUGERAH PERDANA: PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI PENJUALAN TERHADAP PEMBELIAN SEPEDA MOTOR HONDA DI CV. TOLITOLI ANUGERAH PERDANA - Angga Prayudha Ashari H. Mallu; I Kadek Galung Mahendra (STIE MUJAHIDIN TOLITOLI, 2024)
This study aims to find out how much influence the influence of product quality, price, and sales promotion on the decision to buy Honda motorcycles on CV. Tolitoli Anugerah perdana. This study uses a quantitative research method with an associative type of research. The data collection techniques in this study are: observation, documentation and questionnaires. Based on the results of the partial hypothesis test, the product quality variable has a significant effect on the decision to buy Honda motorcycles on CV. Anugerah Perdana Tolitoli which is seen as a value of Sig. 0.000 < 0.05 and a calculated t-value of 3.652 > a t-value of 1.979 table until the H1 hypothesis is accepted. The results of the hypothesis test of price variables have a significant effect on purchase decisions are evidenced by the value of Sig.0.000 < 0.05 and the t-value of 3.929 > 1.979 so that H2 is accepted. The results of the hypothesis test of the sales promotion variable had a significant effect on the purchase decision with a value of Sig.0.000 < 0.05 and a t-value of 7.685 > 1.979 so that H3 was accepted. And the results of the hypothesis test simultaneously, product quality variables, prices, and sales promotions have a significant effect on the decision to buy Honda motorcycles on CV. Tolitoli Anugerah perdana. This is proven by the results of the F test where the Sig. value is 0.000 < 0.05 and the F value is calculated 64.343 > the F value of table 2.68.